Pengaruh Faktor Fundamental Perusahaan Terhadap Price to Book Value - Rahayu, Maryati; Sari, Bida (IAIN Surakarta, 2020)
The purpose of this study was to analyze factors that affect Price to Book Value, by taking samples to manufacturing companies the industrial sector consumer goods who registered at the indonesian stock exchange the period 2015 – 2018 as many as 15 company. Based on t-test known investment decision which are proxied by price earn- ing ratio, capital structure which are proxied by debt to equity ra- tio, profitability which are proxied by return on asset ratio and size that influence the price to book value significanly. While institutional ownership have no effect on price to book value. Based on ANOVA test (F-test)) there are significant influences of investment decision, capital structure (DER), profitability (ROA), institutional owner- ship and size on the price to book value. The results of the coefficient of determination it can be concluded that the fifth of the independent variable affecting price to book value of 59,5%, while the rest 40,5% can be explained by other factors that is not incorporated into research. Keywords: PER, DER, ROA, Institutional Ownership,Size, Price to Book Value JEL Classification: G23, L25, L60, M41, O16, L69